2018
DOI: 10.1016/j.cmet.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Inosine Monophosphate Dehydrogenase Dependence in a Subset of Small Cell Lung Cancers

Abstract: Small cell lung cancer (SCLC) is a rapidly lethal disease with few therapeutic options. We studied metabolic heterogeneity in SCLC to identify subtype-selective vulnerabilities. Metabolomics in SCLC cell lines identified two groups correlating with high or low expression of the Achaete-scute homolog-1 (ASCL1) transcription factor (ASCL1 and ASCL1), a lineage oncogene. Guanosine nucleotides were elevated in ASCL1 cells and tumors from genetically engineered mice. ASCL1 tumors abundantly express the guanosine bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
153
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 56 publications
5
153
1
Order By: Relevance
“…SCLC cell dependency on high PK activity appears much greater than that of other cancer types, suggesting that SCLC cells have unique metabolic properties and are particularly vulnerable to down-modulation of PK activity. Relevant to this, Huang F. et al recently reported an interesting metabolic feature of SCLC, namely, inosine monophosphate dehydrogenase dependence, although this property was only seen in a minor subset (ASCL1 low ) of these cancers [10]. Better understanding of SCLC cell metabolism is needed to devise novel therapeutic strategies to treat this aggressive malignancy, which harbors few druggable mutations.…”
mentioning
confidence: 99%
“…SCLC cell dependency on high PK activity appears much greater than that of other cancer types, suggesting that SCLC cells have unique metabolic properties and are particularly vulnerable to down-modulation of PK activity. Relevant to this, Huang F. et al recently reported an interesting metabolic feature of SCLC, namely, inosine monophosphate dehydrogenase dependence, although this property was only seen in a minor subset (ASCL1 low ) of these cancers [10]. Better understanding of SCLC cell metabolism is needed to devise novel therapeutic strategies to treat this aggressive malignancy, which harbors few druggable mutations.…”
mentioning
confidence: 99%
“…Steady‐state metabolomic profiling in collaboration with Ralph DeBerardinis's laboratory has shown that C‐MYC–driven tumors are metabolically distinct from L‐MYC–driven tumors . C‐MYC–driven tumors show an enrichment in nucleotide biosynthesis and arginine metabolism .…”
Section: Arginine Dependence Of Myc‐driven Lung Cancermentioning
confidence: 99%
“…Their expression levels can be used to define SCLC molecular subsets that have distinct metabolic profiles. In SCLC cell lines as well as tissue samples from treatment‐naive patients, ASCL1 low /C‐MYC high tumors had abundant purine nucleotides …”
Section: Upregulating Purine Synthesis In Sclcmentioning
confidence: 99%
See 2 more Smart Citations